Mitigating functional fatigue of 3D-printed nickel-titanium shape memory alloy using hybridizing stabilizers - Ojo Philip Bodunde; Shiming Gao; Shuo Qu; Junhao Ding; Xu Song; Wei-Hsin Liao (Results in Engineering)
Nickel-titanium shape memory alloy (NiTi SMA) is the most used of all shape memory materials. They are often posed with the threat of poor machinability and in-process fatigue during real-time engineering applications. In this study, pre-optimised compositions of NiTi and α, β, and γ stabilizers were used to fabricate simple geometries of NiTi-α, NiTi-β, and NiTi-γ for fatigue testing. The shape memory property of the hybrid form of NiTi SMAs were modelled and simulated to observe possible deviation from the bare NiTi SMA. Modelling and numerical simulations were also performed to simulate the numbers of cycles to fatigue failure and the corresponding damage due to slip. The numerical fatigue behaviour of the hybrid NiTi SMA was simulated using two control strategies i.e. stress and strain control strategies. Simulations and empirical estimations were experimentally validated via differential scanning calorimetry (DSC) for shape memory behaviour, and mechanical testing on the MTS for cyclic fatigue behaviours. The follow-up experiments made NiTiCuo, the most suitable hybrid and the best control strategies for fatigue evaluation is the strain. And the numbers of cycle to fatigue failure ranges between 3500 and 4000 for NiTi-α; 1500 and 2000 for NiTi-β; and like bare NiTi, 1000 and 1500 for NiTi-γ. Details of microstructure were given and its information could be helpful for those who require hybridized NiTi alloys for various applications.